Reduced Osteoarthritis Severity in Aged Mice With Deletion of Macrophage Migration Inhibitory Factor. Issue 2 (28th January 2017) - Rowe, Meredith A.; Harper, Lindsey R.; McNulty, Margaret A.; Lau, Anthony G.; Carlson, Cathy S.; Leng, Lin; Bucala, Richard J.; Miller, Richard A.; Loeser, Richard F.
Abstract : Objective: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine that is elevated in the serum and synovial fluid of patients with osteoarthritis (OA). This study was undertaken to investigate the potential role of MIF in OA in human joint tissues and in vivo in mice with age‐related and surgically induced OA. Methods: MIF in conditioned media from human chondrocytes and meniscal cells and from cartilage explants was measured by enzyme‐linked immunosorbent assay. The severity of OA was analyzed histologically in male wild‐type and MIF −/− mice at 12 and 22 months of age and following destabilization of the medial meniscus (DMM) surgery in 12‐week‐old MIF −/− mice as well as in wild‐type mice treated with a neutralizing MIF antibody. Synovial hyperplasia was graded in S100A8‐immunostained histologic sections. Bone morphometric parameters were measured by micro–computed tomography. Results: Human OA chondrocytes secreted 3‐fold higher levels of MIF than normal chondrocytes, while normal and OA meniscal cells produced equivalent amounts. Compared to age‐ and strain‐matched controls, the cartilage, bone, and synovium in older adult mice with MIF deletion were protected against changes of naturally occurring age‐related OA. No protection against DMM‐induced OA was seen in young adult MIF −/− mice or in wild‐type mice treated with anti‐MIF. Increased bone density in 8‐week‐old mice with MIF deletion was not maintained at 12 months. Conclusion: These results demonstrate a differential mechanism in the pathogenesis of naturally occurring age‐related OA compared to injury‐induced OA. The inhibition of MIF may represent a novel therapeutic target in the reduction of the severity of age‐related OA.